2022
DOI: 10.1177/20552076221129718
|View full text |Cite
|
Sign up to set email alerts
|

Effects of personalization and source expertise on users’ health beliefs and usage intention toward health chatbots: Evidence from an online experiment

Abstract: Objective Based on the heuristic–systematic model (HSM) and health belief model (HBM), this study aims to investigate how personalization and source expertise in responses from a health chatbot influence users’ health belief-related factors (i.e. perceived benefits, self-efficacy and privacy concerns) as well as usage intention. Methods A 2 (personalization vs. non-personalization) × 2 (source expertise vs. non-source expertise) online between-subject experiment was designed. Participants were recruited in Chi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(1 citation statement)
references
References 96 publications
(151 reference statements)
0
0
0
Order By: Relevance
“…G*Power was employed to provide an estimate for an appropriate sample size [15]. Based on the data from previous experimental studies regarding personalisation and user behaviour [28,32], we estimated the effect size to be 0.23. The estimate indicated that 360 participants were needed in this research to achieve a significance criterion of 5% and 90% power.…”
Section: Data Collection and Participantsmentioning
confidence: 99%
“…G*Power was employed to provide an estimate for an appropriate sample size [15]. Based on the data from previous experimental studies regarding personalisation and user behaviour [28,32], we estimated the effect size to be 0.23. The estimate indicated that 360 participants were needed in this research to achieve a significance criterion of 5% and 90% power.…”
Section: Data Collection and Participantsmentioning
confidence: 99%